Increasing Students' Reading Skills Using Reading Box in Junior High School - E. Ar, Nur Azizah; Syam, Andi Tenrisanna; Madehang; Masruddin; Husnaini (Institut Agama Islam Negeri Palopo, 2024)
Reading skills are important for personal and academic success, and they provide numerous benefits, including increased knowledge, improved communication skills, enhanced imagination and creativity, reduced stress and depression, academic success, critical thinking skills, and a lifelong love of learning. This study aims to determine whether or not the reading box media effectively improve the student`s reading skills at SMPIT Al-Hafizh Palopo. This study applied the pre-experimental method. The population in this study consists of twelve students, and the sample was chosen using the total sampling technique, with the total number being 12 students. The writer collected the data through pre-test and post-test. SPSS 20 edition was used to perform statistical analysis on the data. The writer revealed that the post-test average score was higher than the pre-test average score (78.16 > 32.16). Besides, the t-count value was higher than the t-table value. The result of the student's scores on the post-test became more elevated than the pre-test representing the treatment's effectiveness in helping the learners improve their reading skills. Therefore, it could be concluded that using the reading box significantly improves the student's reading skills, especially in narrative text.Â